2022
DOI: 10.1088/1873-7005/ac421b
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy simulation of tracer gas dispersion in a cavity

Abstract: This paper assesses the prediction of inert tracer gas dispersion within a cavity of height (H) 1.0 m, and unity aspect ratio, using large Eddy simulation (LES). The flow Reynolds number was 67 000, based on the freestream velocity and cavity height. The flow upstream of the cavity was laminar, producing a cavity shear layer which underwent a transition to turbulence over the cavity. Three distinct meshes are used, with grid spacings of H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The LES results reported here are performed using the OpenFOAM v2112 solver suite (www.openfoam.com). The open-source CFD software suite has been used extensively in the study of urban environment flows (Jeanjean et al 2015, Zhong et al 2015, García-Sánchez et al 2018, Kikumoto and Ooka 2018, McMullan 2022, McMullan and Angelino 2022. The filtered variables are stored on a collocated grid, and the governing equations are solved using a PIMPLE algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LES results reported here are performed using the OpenFOAM v2112 solver suite (www.openfoam.com). The open-source CFD software suite has been used extensively in the study of urban environment flows (Jeanjean et al 2015, Zhong et al 2015, García-Sánchez et al 2018, Kikumoto and Ooka 2018, McMullan 2022, McMullan and Angelino 2022. The filtered variables are stored on a collocated grid, and the governing equations are solved using a PIMPLE algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Many such models exist in the literature, with the Smagorinsky model (Smagorinsky 1963), the WALE model (Nicoud and Ducros 1999), and the Germano-Lilly model (Germano et al 1991, Lilly 1992, being the most commonly used for USC/cavity flows (Tominaga et al 2008, Cheng and Liu 2011, Kikumoto and Ooka 2018. LES has been extensively used to simulate cavity-type flows at isothermal conditions (Li et al 2009, Han et al 2018, Kikumoto and Ooka 2018, McMullan 2022, where it has been shown that the vortex structure within the cavity is captured using LES (Cui et al 2004), and that the aspect ratio of the cavity plays a key role in the topology of the vortex structure within it (Li et al 2008). LES studies of the cavity-type flow at thermally stratified conditions are less common in the literature, with both unstable stratification conditions (Li et al 2010, Park et al 2012, and stable stratification conditions considered (Li et al 2015(Li et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the heated windward wall could cause a multi-vortex structure within the canyon. When the walls are cooled, the evolution of the shear layer is delayed, leading to stagnant flow in the bottom part of the canyon [49]. Chew et al compared the RANS and LES at reduced and full scales.…”
Section: Introductionmentioning
confidence: 99%
“…The LES method can effectively obtain the real transient flow field information, and can be used to predict complex flows such as separation and transition. And the LES framework has been widely used in the study of ventilated cavity flows (Hughes et al 2001, Yu et al 2020, Shen et al 2022, McMullan 2022, and good results have been obtained. In this study, there are obvious entrainment and shedding phenomena in the ventilated cavity, in order to better obtain the internal flow field information, the LES turbulence model is used in this paper.…”
Section: Introductionmentioning
confidence: 99%